Behaviour of austenitic stainless steel bolts at elevated temperatures. (15th May 2021) - Wang, Hui; Hu, Ying; Wang, Xing-Qiang; Tao, Zhong; Tang, Sheng-Lin; Pang, Xiao-Ping; Chen, Yohchia Frank
Highlights: Experimental and analytical investigations carried out for A2-70 bolts in fire. The reduction equations developed for material parameters of A2-70 bolts in fire. Full-range stress-strain model formulated for austenitic stainless steel bolts in fire. Behavioural comparison of stainless steel and high-strength bolts exposed to fire. Abstract: Stainless steel bolts have an underlying use in bolted connections, as they possess more significant material properties and resistance than high-strength bolts under fire and/or corrosion conditions. Appropriate estimation for fire safety design of these connections depends largely on the ability to accurately predict the fundamental material response at elevated temperatures. Currently, although residual properties of different stainless steels have been excessively investigated using experimental and analytical methods at elevated temperatures, the mechanical behaviour of stainless steel bolts exposed to fire is much less attentively scrutinized than that of high-strength steel bolts. Thus an elevated temperature experimental investigation was conducted to exhibit discrete reduction factors and continuous stress–strain response for A2-70 stainless steel bolts. Test results indicated that the currently available reduction factors or equations of A2-70 base materials (EN1.4301 equivalent to SUS304) are incapable of providing a more accurate representation of residual properties for A2-70 stainless steel bolts subjected to the cold-forging effect. Hence, for A2-70 residual properties of Young's modulus, yield strength, ultimate strength, ultimate strain and strain-hardening exponent, their regression-based reduction equations were developed to accommodate test data, respectively. Hereafter, in conjunction with five proposed reduction equations, the full-range measured stress–strain curves of A2-70 stainless steel bolts were evaluated using five ambient temperature mechanical parameters based on a modified material model with a necking stage at elevated temperatures, thus the predicted stress–strain curve up to the ultimate stress can correlate well with stress–strain curves of replicate tests at a given temperature, while the necking segment can be predicted approximately and quantitatively after the peak stress.